Cold Shock Proteins: A Minireview with Special Emphasis on Csp-family of Enteropathogenic Yersinia - Keto-Timonen, Riikka; Hietala, Nina; Palonen, Eveliina; Hakakorpi, Anna; Lindström, Miia; Korkeala, Hannu (Frontiers in Microbiology, 2016)
Bacteria have evolved a number of mechanisms for coping with stress and adapting to changing environmental conditions. Many bacteria produce small cold shock proteins (Csp) as a response to rapid temperature downshift (cold shock). During cold shock, the cell membrane fluidity and enzyme activity decrease, and the efficiency of transcription and translation is reduced due to stabilization of nucleic acid secondary structures. Moreover, protein folding is inefficient and ribosome function is hampered. Csps are thought to counteract these harmful effects by serving as nucleic acid chaperons that may prevent the formation of secondary structures in mRNA at low temperature and thus facilitate the initiation of translation. However, some Csps are non-cold inducible and they are reported to be involved in various cellular processes to promote normal growth and stress adaptation responses. Csps have been shown to contribute to osmotic, oxidative, starvation, pH and ethanol stress tolerance as well as to host cell invasion. Therefore, Csps seem to have a wider role in stress tolerance of bacteria than previously assumed. Yersinia enterocolitica and Yersinia pseudotuberculosis are enteropathogens that can spread through foodstuffs and cause an enteric infection called yersiniosis. Enteropathogenic Yersinia are psychrotrophs that are able to grow at temperatures close to 0ºC and thus they set great challenges for the modern food industry. To be able to efficiently control psychrotrophic Yersinia during food production and storage, it is essential to understand the functions and roles of Csps in stress response of enteropathogenic Yersinia.